Green Synthesis of Chitosan-Assisted ZnO Nanoparticles and Their Photocatalytic Application in ZnO/TiO₂ Composites for Isopropanol Degradation - Le H. Hoang; Ho G. Quynh; Mai H. Nghi; Nguyen T. T. Phuong; Ngo T. H. Duong; Nguyen Quang Long (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Nano-sized ZnO particles were successfully synthesized via a green, efficient, and chitosan-assisted method, which is both cost-effective and environmentally friendly. The nanoscale characteristics of the synthesized particles were confirmed through various analytical techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen adsorption–desorption isotherms, diffuse reflectance spectroscopy (DRS), and Fourier-Transform Infrared Spectroscopy (FTIR). This study primarily investigated the photocatalytic performance of ZnO/TiO₂ composites prepared by a simple mechanical mixing approach for the degradation of isopropanol (IPA) in a continuous-flow system under UVA irradiation at room temperature. A range of experimental conditions, including initial IPA concentrations, gas flow rates, relative humidity levels, and the number of UV lamps, were systematically explored. The mechanically mixed ZnO/TiO₂ nanomaterial exhibited enhanced photocatalytic activity compared to pure ZnO. Notably, while commercial TiO₂ showed reduced IPA removal efficiency under humid conditions, the ZnO/TiO₂ composite maintained superior performance, achieving a removal efficiency of 45% over a 3-hour period at 30% relative humidity with an inlet IPA concentration of about 1200 ppmv, a flow rate of 3 L/h, and illumination by four UV lamps. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).